MCM2-7 ring closure involves the Mcm5 C-terminus and triggers Mcm4 ATP hydrolysis - Sarah V. Faull; Marta Barbon; Audrey Mossler; Zuanning Yuan; Lin Bai; L. Maximilian Reuter; Alberto Riera; Christian Winkler; Indiana Magdalou; Matthew Peach; Huilin Li; Christian Speck (Nature Communications)
Abstract The eukaryotic helicase MCM2-7, is loaded by ORC, Cdc6 and Cdt1 as a double-hexamer onto replication origins. The insertion of DNA into the helicase leads to partial MCM2-7 ring closure, while ATP hydrolysis is essential for consecutive steps in pre-replicative complex (pre-RC) assembly. Currently it is unknown how MCM2-7 ring closure and ATP-hydrolysis are controlled. A cryo-EM structure of an ORC-Cdc6-Cdt1-MCM2-7 intermediate shows a remodelled, fully-closed Mcm2/Mcm5 interface. The Mcm5 C-terminus (C5) contacts Orc3 and specifically recognises this closed ring. Interestingly, we found that normal helicase loading triggers Mcm4 ATP-hydrolysis, which in turn leads to reorganisation of the MCM2-7 complex and Cdt1 release. However, defective MCM2-7 ring closure, due to mutations at the Mcm2/Mcm5 interface, leads to MCM2-7 ring splitting and complex disassembly. As such we identify Mcm4 as the key ATPase in regulating pre-RC formation. Crucially, a stable Mcm2/Mcm5 interface is essential for productive ATP-hydrolysis-dependent remodelling of the helicase.